Etnopedagogi Berlandaskan Nilai-Nilai Rumah Betang dalam Pembelajaran Sosiologi - Alif Alfi Syahrin; Bunga Mustika (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
Betang house is a traditional house of Dayak ethnicity which has various values that behavein life. Betang house values are part of the character of the Indonesian people so that theycan be implemented in sociology subjects based on ethnopedagogy.This research uses aliterature study method based on various relevant documents. The results of this studyindicate that in implementing the values of betang houses in class X, XI and XI materials canmake students have character that is sourced from the values of local wisdom in their area,especially in West Kalimantan Province.Furthermore, the use of learning models in sociologysubjects is the use of learning models that are tailored to each material taught to studentssuch as the material in class X and XII used models of lecture and discussion learning.Whilethe class XI material uses the role playing learning model in material about community andmulticultural groups as an effort to provide students with an understanding of local wisdomand efforts to revitalize the values of the Betang house towards social life.